Assessment of Students’ Creative Thinking Skill on the Implementation of Project-Based Learning - Sari, Eka Dyah Puspita; Trisnawati, Ririn Kurnia; Agustina, Mia Fitria; Adiarti, Dian; Noorashid, Najib (International Journal of Language Education, 2023)
The implementation of Merdeka Belajar – Kampus Merdeka (Freedom to Learn) in Indonesia urges universities to adapt and set changes in learning activities. One of the changes is the implementation of Project-Based Learning to increase students’ activeness and creativity. This research aims to assess students’ creative thinking on the implementation of Project-Based Learning. This research was a descriptive case study with a qualitative approach. Purposive sampling was chosen in this research because the sample was chosen on purpose, i.e., those who joined literary criticism class. There were ten students who played as the subject of the research. It used observation sheets and questionnaires to obtain the data. The data were then analyzed to get reliable results of students’ creative thinking assessment. The result showed that some students (40%) strongly agreed that they faced some difficulties in developing their creative thinking. Most of their problems were about developing ideas into coherence text, structuring or organizing a good text, and choosing appropriate vocabulary to avoid repetition in the text. Students also found that project-based learning allowed them to develop their creative thinking in forms of independence, confidence, creativity, tolerance, and leadership. Regarding the result, it can be concluded that project-based learning is proven to be beneficial in developing students’ creative thinking, though they find some obstacles during the process.